Legal Consequences Of The Icj's Decision In The Nicaragua V. Colombia Case On The Pact Of Bogota - Alvina Alvina; Ida Kurnia (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
International agreements in the practice of diplomatic relations are an important aspect. Where in its implementation, the role of international agreements in international law is based on the fact that international law mostly consists of international treaties. One example of an international treaties is the Pact of Bogota. The Pact of Bogota is the United States Agreement on the Settlement of the Pacific region signed by the independent American republics that gathered at the Ninth International Conference of American States in Bogota, Colombia. One of the member countries of this pact is Nicaragua and Colombia. The International Court of Justice from November 19, 2012, based on the Pact of Bogota agreement. The issue raised by the author is related to the decision of the international court in deciding cases between Nicaragua and Colombia based on the Pact of Bogota with the consideration that Colombia had withdrawn from the Pact of Bogota before Nicaragua filed a lawsuit to the International Court of Justice, namely on November 27, 2012.